FAKTOR YANG MEMPENGARUHI PENERIMAAN DAERAH KOTA DKI JAKARTA TAHUN 2012-2019 - Veren Fabiola; Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This study aims to see how the effect of hotel, parking, and groundwater taxes toward Original Regional Income of DKI Jakarta City 2012-2019. The research data processing technique uses multiple regression analysis assisted by the SPSS (Statistical Program for Social Sciences) version 25.00. This research was conducted based on the planning and realization data of the city of DKI Jakarta in 2012-2019. The results on this study indicate that hotel have a significant influence on local revenue. While parking and groundwater taxes didn’t have influence on local revenue. Further research is suggested to do different tests and grouping of years and add other variables that affect local revenue.